HARMONY AMIDST DIVERSITY: EXPLORING RELIGIOUS PLURALISM IN BENGAL THROUGH THE LENS OF SUFI HERITAGE AND ITS ENVOYS - DR. SAEYD RASHED HASAN CHOWDURY (Hamdard Islamicus)
This study explores the significant influence of Sufism on Bengal’s cultural, religious, and social landscape from the eleventh century to the present. It highlights the contributions of pivotal Sufi figures like Shah Jalal, Shah Paran, and other Sufi orders who played crucial roles in propagating Islam and fostering regional socio-economic development following the 1204 CE conquest by Ikhtiyaruddin Muhammad bin Bakhtiyar Khilji. By establishing khanqahs, these Sufis provided religious instruction and spiritual guidance and promoted tolerance and moderation within Bengal’s diverse society. Utilising a qualitative methodology, the research draws on primary and secondary data from local and international archives to underscore Sufism’s enduring impact on interfaith harmony and societal cohesion in Bengal. While much literature exists on Sufism in Bengali, academic research is scarce. This study aims to fill that gap by offering a nuanced analysis that emphasises both the positive contributions of genuine Sufi scholars (e.g. coexistence of multiple religions) and the problematic actions of pseudo-Sufi groups engaged in non-Islamic practices (e.g. shirk, bi‘dah and altered false beliefs). This dual focus enhances the academic understanding of Sufism’s complex legacy in the region.